Penerapan PLTS Sebagai Sumber Energi Listrik Untuk UMKM Kerupuk Wanita Tani di Desa Tanjung Karawang - Dika Satria; Clara Virnanda Asmara Putri; Mery Athonia Nasta Latu; Elisa Athonia Bangun; Agus Sutiyana (LPPM IT Telkom Purwokerto, 2024)
This community service aims to implement a solar photovoltaic system (PLTS) as a reliable and sustainable source of electrical energy for Micro, Small and Medium Enterprises (MSMEs) Kerupuk Wanita Tani in Tanjung Karawang Village. The method used in this activity is implementation planning and training for PLTS installation. The results of this activity show that the Kerupuk Wanita Tani MSME has a PLTS system that can meet its electrical energy needs independently. The impact of this activity is to increase the productivity of Tanjung Village Women Farmers' MSMEs, provide electricity access to Tanjung Village PAUD and street lighting for residents. Apart from that, installing PLTS can increase community understanding to participate in implementing PLTS as an energy independent village in an effort to reduce greenhouse gas emissions.